2020
DOI: 10.3400/avd.oa.20-00114
|View full text |Cite
|
Sign up to set email alerts
|

Results of Stenting for Central Venous Occlusions and Stenoses in the Hemodialysis Patients

Abstract: Objectives: We aim to investigate the results of stenting for central venous occlusions and stenoses in the hemodialysis patients. Methods: Twenty-nine cases treated with endovascular recanalization with deployment of bare metal stent (BMS) for central venous occlusions (24 cases) and recurrent stenoses (5 cases) between 2014 and 2018 were retrospectively analyzed. Results of these procedures including success rate, operative time, estimated blood loss, morbidity, primary patency, assisted primary patency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…2 One year stent patency in this setting exceeds 70%. 3 The self-expanding Wallstent is one option to treat central venous lesions and is intended to treat residual stenoses ≥30% for veins ≤10 mm in diameter and ≥50% for veins ≥10 mm in diameter for innominate and subclavian veins 8–15 mm in size that have previously failed balloon angioplasty. The unique braided wire scaffold design gives the stent a high degree of conformability and strength.…”
Section: Discussionmentioning
confidence: 99%
“…2 One year stent patency in this setting exceeds 70%. 3 The self-expanding Wallstent is one option to treat central venous lesions and is intended to treat residual stenoses ≥30% for veins ≤10 mm in diameter and ≥50% for veins ≥10 mm in diameter for innominate and subclavian veins 8–15 mm in size that have previously failed balloon angioplasty. The unique braided wire scaffold design gives the stent a high degree of conformability and strength.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical treatment of central venous lesions has yielded good results, surgical procedures are more invasive than endovascular treatments and are usually not the first choice for therapy (14,15). Endovascular treatment remains the mainstay of treatment in hemodialysis of patients with CVO, with good efficacy and safety (3,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…1,[7][8][9][10][11][12][13][14][15] In our case, surgical ligation or obstruction was deemed implausible due to edema surrounding the AV shunt. Moreover, Eguchi and Honma reported that 69% of the case did not require reintervention for the original lesion 1 year after the stent placement against central venous lesion, 16) whereas Ashwal et al also reported that 33% did not require recurrent stenosis or reintervention 1 year after the endovascular therapy (i.e., percutaneous transluminal angioplasty with or without stent placement) for central venous lesion. 17) Given these low patency rates, the approach reported herein may be one of the potential alternatives for intervention against symptomatic CVD.…”
Section: Discussionmentioning
confidence: 99%